2010
DOI: 10.1051/forest/2009090
|View full text |Cite
|
Sign up to set email alerts
|

The effects of forest structure on the risk of wind damage at a landscape level in a boreal forest ecosystem

Abstract: Keywords:critical wind speed / forest edges / mechanistic model / Monte Carlo simulation / risk of wind damage Abstract • The aim of this work was to analyze how the forest structure affects the risk of wind damage at the landscape level in a boreal forest.• This was done by employing: (i) Monte Carlo simulation technique for generating landscapes with different age class distributions, proportions of open areas (gaps), and tree species composition; and (ii) a mechanistic wind damage model, HWIND, for predicti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 24 publications
2
37
0
1
Order By: Relevance
“…Valinger and Fridman (2011) also got similar results when they evaluated the risk for damage after the 2005 storm in Sweden, namely 46% of the spruce risk for pine and 2% for broad leafed. From the HWIND runs by Zeng et al (2010) it can be interpreted that the sensitivity of pine is 62% of that of spruce, but this number does not take into account that spruce often grow on soils that promote less stable trees. By analysing storm damage in a periphery district of the 1999 storm in south-western Germany, Kohnle and Gauckler (2003) found that the vulnerability for some hard-wood species was 6-20% of the value for spruce.…”
Section: Allometric-relationship Index For the Cohortsmentioning
confidence: 99%
“…Valinger and Fridman (2011) also got similar results when they evaluated the risk for damage after the 2005 storm in Sweden, namely 46% of the spruce risk for pine and 2% for broad leafed. From the HWIND runs by Zeng et al (2010) it can be interpreted that the sensitivity of pine is 62% of that of spruce, but this number does not take into account that spruce often grow on soils that promote less stable trees. By analysing storm damage in a periphery district of the 1999 storm in south-western Germany, Kohnle and Gauckler (2003) found that the vulnerability for some hard-wood species was 6-20% of the value for spruce.…”
Section: Allometric-relationship Index For the Cohortsmentioning
confidence: 99%
“…Moreover, tree susceptibility to wind and snow damage depends on many physical and ecological factors including: (1) soil characteristics, slope and climate (Copeland et al 1996, Moore 2000, Quine 2000, Talkkari et al 2000, Cucchi & Bert 2003, Zeng et al 2010; (2) species composition, density, diameter distribution, and vertical structure (Valinger et al 1993, Quine 1995; and (3) the morphological and structural characteristics of individual plants (Coutts 1983, Petty & Swain 1985, Gardiner et al 1997, Mitchell 2000, Wilson & Oliver 2000, Nicoll et al 2006, Peltola 2006. The first factor is not influenced by management and cannot be controlled by foresters, the second factor can be controlled only in the long term, the third factor can be very useful in short-term management planning.…”
Section: Introductionmentioning
confidence: 99%
“…This operation can cause an initial disruption in the crown coverage. Consequently, it is important to evaluate the vigor of the crown and the social status of each tree before proceeding with a silvicultural treatment similar to thinning from above.Moreover, tree susceptibility to wind and snow damage depends on many physical and ecological factors including: (1) soil characteristics, slope and climate (Copeland et al 1996, Moore 2000, Quine 2000, Talkkari et al 2000, Cucchi & Bert 2003, Zeng et al 2010; (2) species composition, density, diameter distribution, and vertical structure (Valinger et al 1993, Quine 1995; and (3) the morphological and structural characteristics of individual plants (Coutts 1983, Petty & Swain 1985, Gardiner et al 1997 Black pine has been used often in central and southern Italy to reforest mountainous areas depleted by the intensive use of natural resources. The main purpose of establishing pine forests in Italy was to protect the soil from excessive erosion, and also to facilitate the natural succession toward mixed forests with deciduous species.…”
mentioning
confidence: 99%
“…Other potential legacies, such as old logging damages that could have enhanced the spread of decay fungi (Vasiliauskas, 2001) and monolayered structure that could be more vulnerable to wind disturbances (Zeng et al 2010), at the present have no evident consequences in the two studied plots. As a consequence we expect that these previously managed stands will reach more advanced stages of development far later than natural stands.…”
Section: Discussionmentioning
confidence: 79%